Investigation of the Relationship between Character Structures and Mental Toughness of High School and University Students Doing Fencing Sports - Ozer Yıldız; İbrahim Bacak (Türk Spor ve Egzersiz Dergisi)
The aim of the research is to examine the relationship between character structures and mental toughness of high school and university students doing fencing sports. Survey model, one of the quantitative research methods, has been used in the study. The sample of the research consisted of 286 active licensed fencing athletes who have competing in the classifications of the Turkish Fencing Federation and studying at high schools and university. As a data collection tool in the study Personal Information Form, Sport Character Scale (SCS) Sport Mental Toughness Questionnaire (SMTQ) has been used. In the data analysis, independent group t-test, one-way analysis of variance (ANOVA) test, Tukey HSD multiple comparison test, Pearson Product-Moment Correlation Coefficient test have been applied. As a result of the research; average of sports character scores of high school and university athletes; gender, age, education level, branch and nationality status variables have found to be significantly different. It has been specified that there wasn’t significant difference in the fencing experience period variable. Mental toughness score averages in sports; gender, age, education level, branch, fencing experience period, nationality status have found to be significantly different. It has been determined that there is a low and moderate positive and significant relationship in some sub-dimensions of the Sports Character Scale and Sport Mental Toughness Questionnaire.